Pengaruh Promosi Dan Testimoni Terhadap Minat Beli Produk Hijab Buttonscraves - Latifatun Nikmah; Wina Yuniarti; Rayhan Gunaningrat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the modern era, Muslim fashion, one of which is the hijab, is experiencing developments every year. Hijab is Muslim clothing that is very popular with Muslim women in Indonesia. This incident happened because Muslim women in Indonesia are aware that wearing the hijab is an obligation. This provides an open space for companies to produce Muslim clothing, especially hijabs, to become the main target market in the country. The purpose of this research is to find out whether promotions and testimonials have an influence on purchasing interest through the mediating variable of consumer trust in Buttonscraves products. There were 51 participants in this study and data was collected through an online survey using a Google form. The sampling technique was carried out using purposive sampling techniques and primary data types, as well as collecting questionnaires. The results of the analysis show that promotions have a significant effect on buying interest, testimonials have a significant effect on buying interest and testimonials have a simultaneous effect on buying interest in Hijab Buttonscraves.